2019
DOI: 10.1101/531509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADAMDEC1 maintains a novel growth factor signaling loop in cancer stem cells

Abstract: Glioblastomas (GBM) are lethal brain tumors where poor outcome is attributed to cellular heterogeneity, therapeutic resistance, and a highly infiltrative nature. These characteristics are preferentially linked to GBM cancer stem cells (GSCs), but how GSCs maintain their stemness is incompletely understood and the subject of intense investigation. Here, we identify a novel signaling loop that induces and maintains GSCs. This loop consists of an atypical metalloproteinase, a disintegrin and metalloproteinase dom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Of note, the stem cell transcription factor ZEB1 regulates N-Cadherin expression, which is associated with EMT and invasion. It is tempting to speculate that N-Cadherin/FGFR1 interactions could constitute a positive feedback loop in GSCs through the activation of ZEB1 and subsequent induction of N-Cadherin and FGFR1 expression [70,72] (see also Section 5.1). NCAMs physically associate with FGFRs and inhibit the high-affinity binding between these receptors and their canonical ligands [56,73].…”
Section: Crosstalk Between Fgfrs and Other Cell Surface Moleculesmentioning
confidence: 99%
See 4 more Smart Citations
“…Of note, the stem cell transcription factor ZEB1 regulates N-Cadherin expression, which is associated with EMT and invasion. It is tempting to speculate that N-Cadherin/FGFR1 interactions could constitute a positive feedback loop in GSCs through the activation of ZEB1 and subsequent induction of N-Cadherin and FGFR1 expression [70,72] (see also Section 5.1). NCAMs physically associate with FGFRs and inhibit the high-affinity binding between these receptors and their canonical ligands [56,73].…”
Section: Crosstalk Between Fgfrs and Other Cell Surface Moleculesmentioning
confidence: 99%
“…This study showed that a targeted expression of PSA-NCAM in C6 glioma cells resulted in increased levels of Olig2, a transcription factor associated with GSCs [75]. While it remains unclear whether this was the result of FGFR transactivation by PSA-NCAM, we have recently shown that OLIG2 can be induced by FGFR1 signaling [72]. Furthermore, the L1-CAM/FGFR1/Anosmin-1 complex regulates neurite branching [76,77,78] and L1-CAM-mediated FGFR1 transactivation induces glioma cell proliferation and motility [79].…”
Section: Crosstalk Between Fgfrs and Other Cell Surface Moleculesmentioning
confidence: 99%
See 3 more Smart Citations